2009
DOI: 10.1210/en.2008-1591
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol at Low Concentrations Acts through Distinct Pathways in Normal Versus Benign Prostatic Hyperplasia-Derived Prostate Stromal Cells

Abstract: The aim of this study was to identify differential responses to low concentrations of 17beta-estradiol (E2) in primary stromal cell cultures derived from either normal organ donors or benign prostatic hyperplasia or hypertrophy (BPH) specimens. Furthermore, we sought to identify the potential mechanism of E2 action in these cell types, through either a genomic or nongenomic mechanism. We initially treated stromal cells derived from five normal prostates or five BPH specimens with low concentrations of E2 (0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
11
1
3
Order By: Relevance
“…176 GPR30 has been localized in the cell membrane and endoplasmic recticulum of various estrogen-sensitive tissues and cell lines 176-178 and to mediate the non-genomic action of E2 in breast, endometrial, and ovarian cancer cells through the activation of Erk1/2 and cAMP pathways. 179;180 GPR30 is expressed in the immortalized normal prostate stroma cell line WPWY-1 but does not appear to mediate the growth response induced by high-dose E2. 181 A recent study demonstrated positive staining of GPR30 in both plasma membrane and cytoplasm in the normal and cancerous prostate, and its predominant expression in the luminal epithelium.…”
Section: Non-canonical Actions Of Estrogen and A New Therapeutic Targmentioning
confidence: 99%
“…176 GPR30 has been localized in the cell membrane and endoplasmic recticulum of various estrogen-sensitive tissues and cell lines 176-178 and to mediate the non-genomic action of E2 in breast, endometrial, and ovarian cancer cells through the activation of Erk1/2 and cAMP pathways. 179;180 GPR30 is expressed in the immortalized normal prostate stroma cell line WPWY-1 but does not appear to mediate the growth response induced by high-dose E2. 181 A recent study demonstrated positive staining of GPR30 in both plasma membrane and cytoplasm in the normal and cancerous prostate, and its predominant expression in the luminal epithelium.…”
Section: Non-canonical Actions Of Estrogen and A New Therapeutic Targmentioning
confidence: 99%
“…It mediates its action through interaction with estrogen receptor (ER). There are three types of estrogen receptors, ER α , ER β , and GPR30 [70]. ER α and GPR30 promote proliferation, whereas ER β has proapoptotic and prodifferentiating functions [70, 71].…”
Section: Estrogen Receptors (Er) and Estrogen Actionmentioning
confidence: 99%
“…There are three types of estrogen receptors, ER α , ER β , and GPR30 [70]. ER α and GPR30 promote proliferation, whereas ER β has proapoptotic and prodifferentiating functions [70, 71]. Prostate stromal cells contain mainly ER α and GPR30 [69].…”
Section: Estrogen Receptors (Er) and Estrogen Actionmentioning
confidence: 99%
“…Perhaps more interesting would be the effect of smER␣KO on prostate metastasis due to ER␣'s role in basement membrane integrity. Stromal ER␣ is already implicated in BPH initiation (10). This is especially poignant, because BPH is characterized by an increase in smooth muscle cells (55).…”
Section: Discussionmentioning
confidence: 99%